Influence of Age of Seedlings and Spacing on Seed Yield and Quality under SRI Cultivation in ES-18 Rice Variety - A. KRISHNA; N.K. BIRADARPATIL; K. MANJAPPA; B.B. CHANNAPPAGOUDAR (Seed Research, 2026)
The Influence of age of seedlings and spacing on seed yield and quality under SRI (system of rice intensification) method of cultivation with ES-18 variety during rabi 2004-05 at two locations viz., Agricultural Research Station (Paddy), Sirsi and Gangavati, Karnataka. The 12 days old seedlings produced more number of tillers per plant, leaf area per plant and dry matter per plant at harvest. Wider spacing of 40 x 40 cm found to have significant influence on growth parameters. The 8 days-old seedlings flowered and matured about four to five days early compared to 25 days-old seedlings. Significantly higher seed yield per ha ((3.27 t) and less spikelet sterility (16.72%) was recorded by 12 days seedlings. The treatment combination of 12 days old seedling with wider spacing recorded maximum seed yield per ha. The 12 days old seedlings and seeds produced under wider spacing recorded significantly high seed quality parameters.